Patient-reported outcomes in clinical HIV care: protocol for a single-centre, multistage, mixed-methods study in Denmark - Merete Storgaard; Michael D Fetters; Ellen Moseholm; Nina Weis; P Paul Chandanabhumma; Olivia Borchmann; Ann-Brit Eg Hansen (BMJ Open, 2023)
Introduction People with HIV-1 (PWH) have worse health-related quality of life (HRQoL) compared with the general population. Using patient-reported outcomes (PROs) may help reorient the focus of HIV care towards improving HRQoL. This study aims to develop, implement and evaluate the use of PROs in HIV care.Methods and analysis This is a Danish single-centre, multistage mixed-methods study consisting of four substudies (studies I–IV). Study I is a qualitative focus group interview study aiming to identify relevant PRO domains, and barriers and benefits to PRO use. Participants are 5–10 PWH and 5–10 HIV healthcare providers (HCPs). Data are thematically analysed. Results will guide the design of a PRO measure (PROM). Study II is a quantitative study aiming to assess PWH’s willingness and ability to engage with PRO. All PWH are consecutively invited to complete the PROMs before their next consultations. Demographic data are collected at enrolment. Differences between PWH who do/do not complete the PROMs are assessed. Study III is a quantitative before-and-after study aiming to assess the impact of PRO use on HCP awareness. Participants are all who complete the PROMs in Study II. In contrast to study II, HCPs are notified of the PROM results. The number of problems documented by the HCP in patients’ medical records during studies II and III are compared using χ2 tests. Multiple regression models are used to identify factors associated with HCP awareness. Study IV is a qualitative study aiming to explore PWH and HCP experiences of using PROs. Participants are 15–20 PWH and 10–15 HCP. Data are collected from participant observation of PRO consultations and individual interviews. Data are analysed thematically.Ethics and dissemination This study is approved by the Danish Data Protection Agency. Participants will provide written consent prior to participation. Results will be published in peer-reviewed journals.